SKRINING HEPATITIS B PADA PENGONSUMSI ALKOHOL DI DESA TAPUNGGAYA KECAMATAN MOLAWE - Firdayanti, Firdayanti; Rahmawati, Nizma; Susanti, Susanti; Aulya, Muhammad Sultanul (LPPM Institut Pendidikan Nusantara Global, 2024)
Hepatitis B is an infection that occurs in the liver caused by the hepatitis B virus (HBV). This disease usually becomes acute or chronic and can also cause liver inflammation, liver cirrhosis, liver cancer, and death. Hepatitis B is an inflammatory process in the liver, popularly known as liver disease, liver disease, or jaundice. The purpose of this study was to determine the results of hepatitis B screening on alcohol consumption in Tapunggaya Village, Molawe District.The type of research used is an analytical observational study which aims to determine the results of hepatitis B screening on alcohol consumption in Tapunggaya Village, Molawe District. The number of samples is 30 blood and the examination method used is immunochromatography (ICT).Based on the results of research from 30 blood samples of alcohol consumers at the Tapunggaya Public Health Center, Molawe District, it was concluded that 30 alcohol consumers (100%) found negative results, 28 people (93%) were found to be positive, 2 people (7%). Infected with the hepatitis B virus.